Ibd 2018
DOI: 10.1136/gutjnl-2018-bsgabstracts.131
|View full text |Cite
|
Sign up to set email alerts
|

PTU-009 Upper gastrointestinal inflammation in patients with immune-checkpoint inhibitor induced diarrhoea

Abstract: moderate-to-severe disease. However, these drugs tend to perform less well in the maintenance of remission. Route of administration may influence efficacy and network meta-analyses of trial data indicate a superiority of intravenous drugs (IV; Infliximab; IFX) over subcutaneous (SC; adalimumab; ADA). We conducted a retrospective multicentre case-control study to compare the efficacy of these two drugs. Methods Patients administered IFX or ADA as their first biologic, identified from therapy databases of five U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In another series, inflammatory changes in the upper GI tract were common in 40 patients with ICPi-induced diarrhoea who underwent OGD and included gastritis (40%) and duodenitis (17.5%). Importantly, even in the absence of macroscopically visible disease, there was a significant burden of microscopic inflammation especially in the duodenum (28%) 50 , which most commonly comprised chronic lymphocytic inflammation and/or increased intraepithelial lymphocytes (86%) with villous atrophy present in 71% 50 . The high yield of inflammatory disease observed in the upper GI tract of patients with upper GI symptoms justifies investigation with OGD and biopsy.…”
Section: Oesophagogastroduodenoscopy (Ogd)mentioning
confidence: 99%
“…In another series, inflammatory changes in the upper GI tract were common in 40 patients with ICPi-induced diarrhoea who underwent OGD and included gastritis (40%) and duodenitis (17.5%). Importantly, even in the absence of macroscopically visible disease, there was a significant burden of microscopic inflammation especially in the duodenum (28%) 50 , which most commonly comprised chronic lymphocytic inflammation and/or increased intraepithelial lymphocytes (86%) with villous atrophy present in 71% 50 . The high yield of inflammatory disease observed in the upper GI tract of patients with upper GI symptoms justifies investigation with OGD and biopsy.…”
Section: Oesophagogastroduodenoscopy (Ogd)mentioning
confidence: 99%
“…Irshaid et al demonstrated that upper GI inflammation is similar to Helicobacter pylori gastritis and celiac disease with minor variations on histology [9]. Above studies support immune dysregulation and activation of T cell lymphocytes as a possible mechanism for the development of upper GI ulcer with ICIs [7][8][9].…”
Section: Discussionmentioning
confidence: 83%
“…Tang et al in their study of 60 patients with endoscopy and biopsy showed a correlation between ICIs and upper GI inflammation after ruling out other risk factors [ 7 ]. Fazal et al in their study of 25 patients showed common upper GI features, which include erythema, edema, and friability [ 8 ]. Irshaid et al demonstrated that upper GI inflammation is similar to Helicobacter pylori gastritis and celiac disease with minor variations on histology [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional findings in the upper GI tract include lymphocytic gastritis (>30 intraepithelial lymphocytes per 100 epithelial cells). In the duodenum, as well as chronic inflammation with a neutrophil, lymphocyte and plasma cell infiltrate, villus blunting and atrophy have also been described [7, 17].…”
Section: Gastrointestinal Toxicitiesmentioning
confidence: 99%